You Say You Want A Revolution : Information Technology and Growth - Morsink, James (IMF Working Papers; Working Paper ;, 2002)
The information technology (IT) revolution has arrived, but how much will it change the world? It has been established that IT is contributing to labor productivity growth through both increases in the levels of IT capital per worker and total factor productivity (TFP) growth in the production of IT equipment. The main outstanding issue is whether IT is contributing to TFP growth more generally. Using data on IT expenditure and production for a broad sample of countries, we find a positive, large, and significant effect of IT expenditure on the acceleration in TFP in the late 1990s and a smaller-and significant-effect of IT production. We also find evidence that the impact of IT expenditure on TFP growth increases over time, suggesting that spillovers materialize gradually. Our results suggest that the increase in IT expenditure across industrial countries during 1995-2000 will eventually lead to an average increase in TFP growth of about one-third of 1 percent per year.